EVALUATION OF THE ACTIVITY AND TOXICITY OF PATIKAN KEBO HERB (EUPHORBIA HIRTA L.) AS AN INDONESIAN MEDICINAL PLANT - MEGAWATI WIDHARNA, RATNA
Plants used as medicine contain pharmacologically active compounds, as well as toxic compounds. In order to fulfill the plant-based-medicine criteria, which comprises characteristic, efficacy and safety; the toxic compounds must be separated from the pharmacologically active compounds. The correlation between dose and response is also our concern in giving the plant-based-medicine. Euphorbia hirta L. (patikan kebo) is used as traditional plant-based medicine with various activity, such as leaves infuse is used as expectorant for bronchitis and asthma, its ground fruit is given to children as laxative and the root infuse is used to cure headache because of sunburnt. Euphorbia hirta L. herb was extracted by ethanol 70%, and then was evaporated and then continued by the successively liquid-liquid extraction by n-hexane, chloroform, ethyl acetate, n-butanol. The biology activity of each fraction was tested by the pharmacological test guidance. Bioactivity test by Brine Shrimp Lethality Test method was used as the early research guidance. From the test, it was grouped into biologically active and might have pharmacological activity group and fractions that marked cytotoxic activity group as the guidance. It was demonstrated that the ethanolic extract; ethyl acetate, n-butanol and water fractions are the pharmacologically active extract and fractions based on the Brine Shrimp Lethality Test, in which the value of LC50 ranged between 30 and 1,000 ppm, that are 163.9; 39.9; 40.7; 58.7 ppm respectively. The pharmacologically active extract and fractions were then evaluated for their antioxidant and anticiabetic activity. The cytotoxic fractions based on Brine Shrimp Lethality Test, n-hexane and chloroform fraction with the value of LC50 under 30 ppm, that are 8.2 ppm dan 8.8 ppm respectively, was continued to test against Raji cell (Burkitt’s Lymphoma) by MTT (3-[4,5- Dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assay. In Indian medicine, Euphorbia hirta L. has been proven as a potential nature antioxidant. Therefore, the author evaluated the extract and fractions of Euphorbia vi hirta L. herb as promising source in health, food and cosmetic industry. In the pharmacological test, ethanolic extract and ethyl acetate fraction had almost similar activity with ascorbic acid at 5 ppm by DPPH method (in vitro). Towards the extract and fraction having highest antioxidant activity in vitro, in vitro antidiabetic activity test (.-glucosidase inhibition) was carried out. It was demonstrated that in the test, the ethanolic extract and ethyl acetate fraction had the IC50 values of 7.97 ± 0.37 µg/ml and 16.14 ± 4.45 µg/ml. This result is the most closest value to 1-deoxynojirimycin as the reference compound, therefore it was continued to the oral glucose tolerance test using various loading (polysaccharides, disaccharide and monosaccharide) to prove their in vivo activity. Meanwhile, n-hexane and water fractions did not inhibit .-glucosidase as the IC50 values were above 25 µg/ml, that are 29.82 ± 3.4 and 28.07 ± 4.62 µg/ml respectively. The active compound isolation of the pharmacologically active ethyl acetate fraction was carried out by column chromatograhy using Sephadex LH-20 as the stationary phase and methanol:water in gradient as mobile phase. The result of the thin layer chromatography was grouped based on the similarity of the thin layer chromatography profile. AU subfraction was eluted further with methanol:water 50:50 and AU176 isolate was obtained, which after structure elucidation was known as quercitrin. The antidiabetes test in vivo by oral ”glucose tolerance” test was carried out subsequently using various carbohydrate loading, starting from amilum 5g/kg of bw, maltose and sucrose 3 g/kg of bw and glucose 2 g/kg of bw. The ”glucose tolerance” test with amylum loading showed that the blood glucose level of mice given with acarbose and ethanolic extract of 0.57 and 0.285 mg/kg of bw differed significantly (p<0.05) to control and their curve of blood glucose evolution were under the control curve, which means that the ethanolic extract has the inhibition towards amylum. The result of the oral ”glucose tolerance” test with maltose and sucrose loading, indicated that acarbose and all the dose of the ethanolic extract and ethyl acetate fraction showed antidiabetic activity and the curve of blood glucose evolution was under the control curve. This result indicated that the tested extract and fraction affected the carbohydrate metabolism and potential to be researched further as antidiabetes medicine. The direction of the regression curve describes the speed of the tested materials to decrease the blood glucose level to normal after the carbohydrate loading. On the other hand, the result of the glucose tolerance test with glucose 2 mg/kg of bw loading demonstrated that only metformin 130 mg/kg of bw, as reference compound, which decreased the blood glucose level to normal faster than the others. From the result, it is shown that the action mechanism of the ethanolic extract and ethyl acetate fraction of Euphorbia hirta L. were predicted to be similar to acarbose action mechanism, which reduce intestinal absorption of starch, dextrin, and disaccharides by inhibiting the action of intestinal brush border .-glucosidase, compared to metformin, which reduce the absorption of glucose from intestine. Therefore, the inhibition mechanism of a drug to carbohydrate could be determined by conducting oral glucose tolerance test with various loading, starting from polysaccharide, disaccharide and monosaccharide. From the oral ”glucose vii tolerance” test with various carbohydrate loading, it could be concluded that the inhibition of Euphorbia hirta L. herb, especially ethanolic extract and ethyl acetate fraction is due to the inhibition of the change of maltose and sucrose to glucose as they demonstrated very less effect of inhibiting glucose absorption to blood, which is confirmed by the glucose tolerance test. While the quercitrin (in vitro .-glucosidase inhibitor IC50 value of 65.38 ± 0.17 µg/ml) contained in the ethyl acetate fraction is an aldose reductase inhibitor. The cytotoxic fractions, n-hexane and chloroform, were tested their cytotoxicity towards Raji cells (Burkitt’s Lymphoma) using MTT assay. The chloroform fraction has no cytotoxic activity against Raji cells as the IC50 values was 40.32 µg/ml. Although the n-hexane fraction was known as cytotoxic fraction in the Brine Shrimp Lethality Test, it was not cytotoxic to Raji cells, due to the IC50 value was above 100 µg/ml, that was 228.97 µg/ml.This might be due to the specifity of the n-hexane fraction, which might be cytotoxic to other cancer cell line, for example myeloma, breast cancer, or colon cancer. From the result, it was known that the cytotoxicy result in Brine Shrimp Lethality Test, was not always cytotoxicity when tested on the cancer cell and vice versa. In the acute toxicity test, it was demonstrated that the ethanolic extract was practically not toxic as the LD50 value was above 5,000 mg/kg of bw. Meanwhile, the ethyl acetate fraction in female mice had the LD50 value of around 4,808 g/kg of bw and in male mice had the LD50 value of 5,000 mg/kg of bw. This showed a difference of safety of the fraction use in different sex. Contributions of the experiment towards the pharmacy knowledge are the approach of scientific-based of the Euphorbia hirta L. herb usage, by Brine Shrimp Lethality Test method was divided into 2 groups, biologically active and might have pharmacological activity group and those of marked cytotoxicity group which is prospective as cytotoxic agent. The evaluation of antidiabetic mechanism of the ethanolic extract and ethyl acetate fractions in this experiment could be shown by giving various carbohydrate, including polysaccharides (amylum), disccharides (maltose and sucrose) and monosaccharide (glucose) in oral ”glucose tolerance” test in vivo, in this research, it was shown that the antidiabetic activity of the ethanolic extract and ethyl acetate fraction inhibited the breakdown of disaccharides to glucose. The acute toxixity test of the ethyl acetate fraction showing antidiabetic activity in female mice had the LD50 value of around 4,808 mg/kg of bw (a little bit toxic) and in male mice had the LD50 value of 5,000 mg/kg of bw (practically not toxic).